Tobacco prevalence among adults in the urban slums of Delhi: results from a cross-sectional survey - Shyam Kanhaiya Saroj; Tushti Bhardwaj; Archana Kaushik (Monaldi Archives for Chest Disease)
Slum areas exhibited a marked prevalence of elevated tobacco consumption rates, prompting the investigation to assess the extent and perspectives of tobacco usage among the residents in these regions. The present study aimed to evaluate the prevalence and attitudes toward tobacco use within five distinct slum localities in close proximity to the tobacco cessation center. During a house-to-house visit, a cross-sectional survey was conducted in five different slum areas, coded as Zone 1 to Zone 5. To ensure a representative sample, 20% of households were randomly selected from each slum. The survey utilized a pre-designed, pretested, and semi-structured questionnaire to collect relevant data. A total of 274 households provided consent to participate in the survey. The variations in tobacco prevalence were observed across all five slums, ranging adult tobacco prevalence from 16.3% to 36.7%. Tobacco use prevalence differed significantly by gender, with 86.1% males and 13.9% females. Smokeless tobacco was the most preferred method of tobacco use. Notably, 43.8% of adult tobacco users expressed their willingness to quit tobacco usage, out of which 22.3% were female. A large proportion (70.4%) of total adult women tobacco users showed their willingness to quit, while the corresponding percentage for men was only 39.5%. This study highlights the high prevalence of tobacco use and the limited awareness of cessation services among users in nearby slums despite the proximity to cessation centers and mandatory tobacco cessation helpline numbers on tobacco packets. However, during the awareness session, individuals exhibited interest in quitting tobacco consumption.